Pengaruh Gaya Belajar dan Kemandirian Belajar terhadap Hasil Belajar Mata Kuliah Sistem Air Conditioner dengan Motivasi Belajar sebagai Variabel Intervening - Al Hazamy, Muhammad Fuad; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the influence of learning styles and learning independence on student learning outcomes in the Air Conditioner System course. In addition to the direct influence, this study also examines the role of learning motivation as a mediating variable in the relationship between learning styles and learning independence on student learning outcomes in the Automotive Engineering Education Study Program. This study uses a quantitative approach with a data collection method through a questionnaire conducted from January to September. Instrument testing and validity were carried out on independent variables (learning styles and learning independence), dependent variables (learning outcomes), and intervening variables (learning motivation). Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with the help of SmartPLS 3 software. The analysis stages include: 1) evaluation of the outer model to test the validity and reliability of the constructs; 2) evaluation of the inner model to assess the relationship between latent constructs; and 3) significance testing through bootstrapping techniques to obtain t-statistics and p-values ​​as the basis for hypothesis testing. The results showed that learning styles had a significant but negative effect on learning outcomes (p = 0.005), while learning independence had a significant and positive effect (p = 0.006). Meanwhile, learning motivation did not play a significant role as a mediating variable in the relationship between learning styles and learning independence on learning outcomes (p = 0.443 and p = 0.491). The results of the study demonstrate that learning styles and learning independence have a direct effect on learning outcomes, but learning motivation cannot mediate the relationship between learning styles and learning independence on learning outcomes.